Science and opinion in decision making: A case study of the food security collapse in Sri Lanka - Akila Wijerathna‐Yapa; Robert J. Henry; Matt Dunn; Christine A. Beveridge (Modern Agriculture)
Abstract Making decisions related to security, whether at the community, national, or regional level, is a highly intricate task. This requires a multi‐criteria decision‐making approach that incorporates inputs from various perspectives, including those of science, culture, economics, sustainability, and climate change. In order to make successful decisions, it is imperative to compare alternatives and rank the consequences and relative impacts associated with each option. Such comparisons and rankings require a careful balance of evidence‐based scientific data and diverse opinions. The recent scenario of the food security collapse in Sri Lanka provides a poignant reminder of the importance of this decision‐making process and the consequences of unacknowledged or unidentified misinformation. Sri Lanka responded to an unexplained health condition and a desire to enter a new sales market by swiftly transitioning to organic farming. However, this abrupt change led to the rapid collapse of Sri Lanka's food supply, a significant decline in GDP, and hardships for both rural and urban communities. While the government eventually reversed its policy, Sri Lanka faced challenges in recovery. It is evident that disinformation and misinformation played a role in this unfortunate situation. This paper offers an in‐depth exploration of the events, underlining the necessity to distinguish between disinformation and misinformation in policy development.